2006
DOI: 10.1002/ppul.20434
|View full text |Cite
|
Sign up to set email alerts
|

Cavitatory lung disease complicating empyema in children

Abstract: Twenty percentage of cases of empyema in our series were complicated by cavitatory lung disease. It is an important complication of childhood empyema associated classically with S. aureus, but these data suggest that S. pneumoniae now appears to be the main cause. There does not seem to be an association with any particular serotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 10 publications
0
37
0
5
Order By: Relevance
“…Cavitation is more frequently reported among patients with concurrent S. pneumoniae pneumonia and bacteremia, which may reflect the greater severity of disease among bacteremic patients (184). Similarly, a recent study of 75 children with empyema or parapneumonic effusion reported that 15 (20%) had associated cavitary lung disease, 13 of whom had evidence of S. pneumoniae infection (304). Because S. pneumoniae and H. influenzae are such common causes of pneumonia, these pathogens may cause a significant fraction of cavitary pneumonias, even though cavitation is relatively rare with these pathogens.…”
Section: Common Bacterial Infectionsmentioning
confidence: 97%
“…Cavitation is more frequently reported among patients with concurrent S. pneumoniae pneumonia and bacteremia, which may reflect the greater severity of disease among bacteremic patients (184). Similarly, a recent study of 75 children with empyema or parapneumonic effusion reported that 15 (20%) had associated cavitary lung disease, 13 of whom had evidence of S. pneumoniae infection (304). Because S. pneumoniae and H. influenzae are such common causes of pneumonia, these pathogens may cause a significant fraction of cavitary pneumonias, even though cavitation is relatively rare with these pathogens.…”
Section: Common Bacterial Infectionsmentioning
confidence: 97%
“…An increasingly recognised sequela of paediatric CAP is necrotising or cavitary pneumonia, which was first described in 1994 [86,87] and has recently been shown to complicate up to 20% of childhood empyema [88]. It is characterised by necrosis and liquefaction of lung parenchyma, which is thought to be secondary to ischaemia caused by thrombosis of intrapulmonary vessels and can culminate in pulmonary gangrene [89] of single or multiple lobes [74,90].…”
Section: Necrotising Pneumoniamentioning
confidence: 99%
“…It is characterised by necrosis and liquefaction of lung parenchyma, which is thought to be secondary to ischaemia caused by thrombosis of intrapulmonary vessels and can culminate in pulmonary gangrene [89] of single or multiple lobes [74,90]. Historically, the primary causative pathogen was thought to be S. aureus [91] but S. pneumoniae, particularly serotypes 1, 3 9V and 14 [88,89], is now the predominant cause, although M. pneumoniae [92], methicillin-resistant S. aureus and PVL strains of S. aureus [93] have also been implicated. Diagnosis is usually made on CT, as plain chest radiographs will not accurately demonstrate the typical disruption of normal parenchymal architecture where multiple airor fluid-filled cavities replace the normal lung tissue [90].…”
Section: Necrotising Pneumoniamentioning
confidence: 99%
“…33 Furthermore, in England, serotypes 1 and 3 were the common serotypes found in children with PPE. 34 Other organisms that cause PPE are methicillin-sensitive Staphylococcus aureus (MSSA), 35,36 methicillinresistant S aureus (MRSA), 29,[37][38][39] S pyogenic, 19,29,38 Haemophilus influenzae type b, 21,40 Mycoplasma pneumoniae, viridians streptococci, and streptococci of Lancefield group F39, 21 Enterobacteriaceae, Klebsiella spp and Pseudomonas aeruginosa, and Yersinia, 21,36 Bacteroides species, Peptostreptococcus, 41 Streptococcus milleri, 38,41 Fusobacterium necrophorum infection (Lemierre syndrome) in older children, 38,43 and Mycobacterium tuberculosis. 21 PPE can be also due to fungal species such as C albicans, C tropicalis, C krusei, C glabrata, 44,45 which can sometimes lead to gastrointestinal perforation.…”
Section: Microbiologymentioning
confidence: 99%